2022
DOI: 10.3390/jcm11123271
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Combination Therapy for Difficulties Waking Up in Non-School-Attending Students

Abstract: School non-attendance due to difficulties waking up is increasing in Japan, and affected students are commonly diagnosed with orthostatic dysregulation (OD); however, OD-associated sleep problems are overlooked. To date, no sleep-medicine-based treatment for wake-up difficulties in non-school-attending students has been established. This study aimed to assess the efficacy of a novel combination therapy for these students. We assessed the combined effect of sleep hygiene guidance, low-dose aripiprazole administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Previous studies on human participants have indicated that patients diagnosed with certain psychiatric disorders accompanied by sleep disorders who received aripiprazole as part of treatment displayed improved daily sleep rhythms ( Takaki and Ujike, 2014 ; Matsui et al, 2017 ; Tashiro, 2017 ; Omori et al, 2018 ; Imanishi et al, 2021 ; Konishi et al, 2022 ). Prior to aripiprazole administration, many patients exhibited delayed sleep onset and sleep patterns similar to those of free-running rhythms ( Matsui et al, 2017 ; Tashiro, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on human participants have indicated that patients diagnosed with certain psychiatric disorders accompanied by sleep disorders who received aripiprazole as part of treatment displayed improved daily sleep rhythms ( Takaki and Ujike, 2014 ; Matsui et al, 2017 ; Tashiro, 2017 ; Omori et al, 2018 ; Imanishi et al, 2021 ; Konishi et al, 2022 ). Prior to aripiprazole administration, many patients exhibited delayed sleep onset and sleep patterns similar to those of free-running rhythms ( Matsui et al, 2017 ; Tashiro, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that aripiprazole administration improves sleep disorder symptoms in humans, particularly those associated with rhythmic abnormalities ( Takaki and Ujike, 2014 ; Matsui et al, 2017 ; Tashiro, 2017 ; Omori et al, 2018 ; Imanishi et al, 2021 ; Konishi et al, 2022 ). In a case report, a female patient with delayed sleep-phase syndrome (DSPS) could entrain to environmental light–dark cycles following aripiprazole treatment, which improved daytime sleepiness and depressive mood ( Takaki and Ujike, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among circadian rhythm sleep-wake disorders (CRSWDs), delayed sleep-wake phase disorder (DSWPD) is particularly disabling for the youth. It has been reported that aripiprazole, a second-generation antipsychotic, advances the sleep phase in DSWPD (Takaki and Ujike, 2014;Tashiro, 2017;Omori et al, 2018;Konishi et al, 2022). Although this needs to be supported by further evidence, it may be a potent therapeutic option.…”
Section: Introductionmentioning
confidence: 96%